(untitled) (Research, Society and Development, 2025)
Palliative care is essential to improving the quality of life of all those facing life-threatening illnesses, preventing and alleviating suffering. This paper aims to report the palliative care approach to a patient with cerebral palsy due to hypoxic-ischemic encephalopathy in a pediatric intensive care unit. Despite advances in pediatrics, which have enabled the survival of children with serious conditions, many of these patients face permanent sequelae that require ongoing care. The palliative approach focuses not only on survival but also on improving quality of life, involving multidisciplinary monitoring. However, the implementation of pediatric palliative care in Brazil remains slow. Many families of children with serious chronic conditions admitted to ICUs have not previously been approached by any professional in an outpatient setting. This often leads to high expectations of a cure, resulting in greater suffering for the families. An early approach to pediatric palliative care is essential to address psychological needs and ensure that patients and their families have a quality of life until the end.